1996
DOI: 10.1002/art.1780391017
|View full text |Cite
|
Sign up to set email alerts
|

Distinct immunologic features of finnish Sjögren's syndrome patients with HLA alleles DRB1*0301, DQA1*0501, and DQB1*0201. Alterations in circulating T cell receptor γ/δ subsets

Abstract: Objective. To determine whether there were differences in the circulating T lymphocyte subsets or clinical features of patients with primary Sjogren's syndrome (SS) who were positive for different HLA alleles.Methods. Two-and three-color flow cytometry analyses were performed, using a whole blood lysing method.Results Submitted for publication Octoher 4, 1995; accepted in revised form April 16, 1996. autoimmune disorders in patients with the HLA-DR3 haplotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…Furthermore, this subgroup was associated with lower levels of circulating Vδ1-positive T cell receptor γ/ δ (TCR γ/δ) cells and higher levels of circulating CD45 Ropositive TCR γ/δ cells [26]. More recently, a Norwegian study revealed an association with HLA DQA1*0501 and DQB1*0201 with the presence of anti-Ro52 kD in patients with primary SS [20].…”
Section: Human Leukocyte Antigen Gene Associationsmentioning
confidence: 97%
“…Furthermore, this subgroup was associated with lower levels of circulating Vδ1-positive T cell receptor γ/ δ (TCR γ/δ) cells and higher levels of circulating CD45 Ropositive TCR γ/δ cells [26]. More recently, a Norwegian study revealed an association with HLA DQA1*0501 and DQB1*0201 with the presence of anti-Ro52 kD in patients with primary SS [20].…”
Section: Human Leukocyte Antigen Gene Associationsmentioning
confidence: 97%
“…In a Finnish study the significant haplotypes were HLA-DRB1*0301-DQA1*0501-DQB1*0201[35]. Two Norwegian studies published in the same year (2001) showed HLA alleles as having association with SS patients with anti-SSA and/or anti-SSB, the alleles identified were DRB1*03-DQB1*02-DQA1*0501 [36] and DRB1*0301 and DRB3*0101 [37].…”
Section: Sjögren’s Syndrome Predisposition To Hlamentioning
confidence: 99%
“…In both diseases it has been reported that the expression level of HLA-DR in the epithelia is high 20,21 and that the proportion of CD4 ϩ Thelper cells in infiltrating cells is high, 22,23 suggesting the existence of a common immunological abnormality. Van De Merwe and colleagues proposed the following onset mechanism: autoantibodies blocking muscarinic receptors, which are involved in contraction of smooth muscles, are produced in patients with Sjögren's syndrome, thus resulting in interstitial cystitis.…”
Section: Discussionmentioning
confidence: 97%